2015
DOI: 10.1097/md.0000000000001804
|View full text |Cite
|
Sign up to set email alerts
|

Visit-to-Visit Glucose Variability Predicts the Development of End-Stage Renal Disease in Type 2 Diabetes

Abstract: The purpose of this study was to examine the association of glucose variability using coefficient of variation of fasting plasma glucose (FPG-CV) and coefficient of variation of glycated hemoglobin (HbA1c-CV) to end-stage renal disease (ESRD) in 31,841 Chinese patients with type 2 diabetes.Patients with type 2 diabetes enrolled in National Diabetes Care Management Program, aged ≧30 years, and free of ESRD (n = 31,841) in January 1, 2002 to December 31, 2004 were included. Extended Cox proportional hazards regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 34 publications
(44 reference statements)
2
39
1
Order By: Relevance
“…Previous work focused on intake of specific nutrients suggests that the associations observed herein could be explained by differences in intake of long-chain ω-3 fatty acids, [35][36][37] carotenoids, vitamins C and B, 38,39 and possibly differences in carbohydrate quality, including intake of added sugars. [40][41][42] The interpretation of the hormone findings is less straightforward. Men with the highest adherence to the Western pattern had higher testosterone levels, assessed as total and free testosterone, compared with men with less adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work focused on intake of specific nutrients suggests that the associations observed herein could be explained by differences in intake of long-chain ω-3 fatty acids, [35][36][37] carotenoids, vitamins C and B, 38,39 and possibly differences in carbohydrate quality, including intake of added sugars. [40][41][42] The interpretation of the hormone findings is less straightforward. Men with the highest adherence to the Western pattern had higher testosterone levels, assessed as total and free testosterone, compared with men with less adherence.…”
Section: Discussionmentioning
confidence: 99%
“…58 Similarly, long-term GV (HbA1c) in T2D has been associated with the risk of developing diabetic nephropathy. 59,60 Also an association between long-term GV (HbA1c) and diabetic retinopathy has been demonstrated in some studies with T1D. 61,62 GV causes inner retinal sensory neuropathy in persons with T1D.…”
Section: Glucose Variability: Hard Outcomes In Persons With and Withomentioning
confidence: 98%
“…55 Among T2DM studies, glucose variability showed a positive association with the progression of DR. 54 A ten-year survey follow-up of diabetes patients in Taiwan showed that visit-to-visit glucose variations in both FPG-CV and HbA1c-CV independently predicted ESRD in patients with T2DM duration >30 years. 56 Some data show that glucose variability, namely, fasting plasma glucose variability, and retinopathy in T2DM patients have a possible connection. 57 To reduce the risk of long-term complications such as DR and DN, maintaining an HbA1c concentration of 7.0% or less is recommended for all patients with diabetes.…”
Section: Dovepressmentioning
confidence: 99%